Emotion regulation of the affect‐modulated startle reflex during different picture categories. (9th June 2015) - Conzelmann, Annette; McGregor, Victoria; Pauli, Paul
Abstract Previous studies on emotion regulation of the startle reflex found an increase in startle amplitude from down‐, to non‐, to up‐regulation for pleasant and unpleasant stimuli. We wanted to clarify whether this regulation effect remains stable for different picture categories within pleasant and unpleasant picture sets. We assessed startle amplitude of 31 participants during down‐, non‐, or up‐regulation of feelings elicited by pleasant erotic and adventure and unpleasant victim and threat pictures. Startle amplitude was smaller during adventure and erotic compared to victim and threat pictures and increased from down‐, to non‐, to up‐regulation independently of the picture category. Results indicate that the motivational priming effect on startle modulation elicited by different picture categories is independent of emotion regulation instructions. In addition, the emotion regulation effect is independent of motivational priming effects.